Metode Project Based Learning Sebagai Solusi dalam Pembelajaran Bahasa Arab Era Covid 19 di MA Rohmaniyyah Demak Tahun Pelajaran 2021/2022 - Marinda Noviani (Uktub: Journal of Arabic Studies, 2022)
The Covid 19 pandemic has forced Arabic teachers to be more creative in choosing learning methods. Arabic as one of the list of difficult subjects and the pandemic period that limits the learning process in schools is a serious problem for Arabic language teachers. Moreover, at the Madrasah Aliyah (MA) level, the learning objectives that must be achieved and the material that must be completed by the Arabic language teacher at the Madrasah Aliyah (MA) level. This research was conducted in class 12 of MA Rohamniyyah Demak. Arabic learning is carried out semi-online or only 50% of the number of students who enter class. Learning Arabic in class 12 MA Rohmaniyyah using the Project Based Learning method. This research uses descriptive qualitative research with research techniques using documentation and interviews. The main subject of this research is the Arabic language teacher. The results of this study are the Project Based Learning method as a solution for learning Arabic in the Covid 19 era at MA Rohmaniyyah Demak. With a semi-online learning process, making the implementation of the Project Based Learning method more effective because the teacher is more focused on observing each student. The Project Based Learning method is a solution for learning Arabic in the Covid 19 era at MA Rohmaniyyah Demak because in its application it can cover the four competencies of learning Arabic, namely, listening (istima'), reading (qiro'ah), speaking (kalam), writing. (book).